1989
DOI: 10.1007/bf00321897
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the neural crest cells in the heart of birds: a three dimensional analysis

Abstract: The distribution of neural crest derived cells (NC) in the heart of quail-chick chimeric embryos was analyzed three-dimensionally after computer reconstruction. During the division of the truncus arteriosus into the aorta and the pulmonary trunk, ventral and dorsal columns of NC-derived cells were found in the truncal swellings. These columns were elongations from the aorticopulmonary (AP) septum. The dorsal column extended more proximally than did the ventral column. Around hatching, NC-derived cells located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 9 publications
0
60
0
Order By: Relevance
“…The origin of the cells within the AP septum is different from that of cushion mesenchymal cells. Migrating cells withhin the AP septum derive from the neural crest (KIRBY et al, 1983;SUMIDA et al, 1989b), and are fibronectin receptor-rich (SUMIDA et al, 1989a). Thus, it is suggested that cells which have the fibronectin receptor migrate into the fibronectin-rich pathways, and cells which have the vitronectin receptor migrate into vitronectin-rich pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the cells within the AP septum is different from that of cushion mesenchymal cells. Migrating cells withhin the AP septum derive from the neural crest (KIRBY et al, 1983;SUMIDA et al, 1989b), and are fibronectin receptor-rich (SUMIDA et al, 1989a). Thus, it is suggested that cells which have the fibronectin receptor migrate into the fibronectin-rich pathways, and cells which have the vitronectin receptor migrate into vitronectin-rich pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These heart cartilages have, however, NC, but not the mesoderm origin at least in birds and mammals (Sumida et al, 1989). Although axolotl belongs to amphibians, the proximity of the anlagen of the heart and the prospective basibranchial 2, both of which show, or cells of different embryonic origin, may indicate a possibility of a cartilaginous differentiation of both NC derived ectomesenchyme and LPM.…”
Section: Chial 2 Cartilagementioning
confidence: 98%
“…They include persistent truncus arteriosus and transposition of the great vessels. In the outflow tract, the cardiac neural crest cells form two opposing spiraling ridges that grow together and eventually merge, dissecting the single outflow tract tube into two vessels, the aorta and the pulmonary artery (Sumida et al, 1989). A distinct population of either neural crest cells or ventrally derived rhombencephalic cells enters the heart at the venous pole.…”
Section: The Cardiac Neural Crestmentioning
confidence: 99%